Gastrointestinal Duplication: 10 Years’ Experience - Mazen O. Kurdi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Gastrointestinal duplication is a rare congenital abnormality. Over the last 10 years, 10 cases of gastrointestinal tract duplication were managed at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Duplications were variable in their level and presentation. The experience in the management of the different levels of gastrointestinal tract duplication will be presented along with a suggested general plan for the management of gastrointestinal duplication based on our experience and the collective experience from different reports in the literature.